2018
DOI: 10.1037/ccp0000345
|View full text |Cite
|
Sign up to set email alerts
|

Lagged effects of substance use on PTSD severity in a randomized controlled trial with modified prolonged exposure and relapse prevention.

Abstract: Objective: To advance understanding the effectiveness of evidence-based treatments for comorbid posttraumatic stress and substance use disorders (PTSD and SUD), research must provide a more nuanced picture of how substance use affects change in PTSD symptoms over the course of treatments, and whether prolonged exposure techniques can be efficacious during active substance use. A dataset that included patients with PTSD/subthreshold PTSD and SUD treated with an exposure-based intervention provided an opportunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…The lack of an association between PTSD severity and subsequent substance use is consistent with studies documenting similar rates and severity of substance use in SUD samples with and without PTSD (Dworkin, Kaysen, Bedard-Gilligan, Rhew, & Lee, 2017;Peirce, Brooner, Kolodner, Schacht, & Kidorf, 2013;Peirce et al, 2016), but contrary to what has been reported in some prospective studies (e.g., Black, Cooney, Sartor, Arias, & Rosen, 2018;Dworkin et al, 2017;Hien et al, 2010). In contrast, self-reported substance use in the present study was moderately associated with more severe PTSD symptoms, which has also been documented in recent studies of exposure-based therapy (Hien et al 2018;Jarnecke et al, 2019). Helping patients reduce or eliminate substance use might have more benefit on their PTSD symptoms than has previously been understood.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The lack of an association between PTSD severity and subsequent substance use is consistent with studies documenting similar rates and severity of substance use in SUD samples with and without PTSD (Dworkin, Kaysen, Bedard-Gilligan, Rhew, & Lee, 2017;Peirce, Brooner, Kolodner, Schacht, & Kidorf, 2013;Peirce et al, 2016), but contrary to what has been reported in some prospective studies (e.g., Black, Cooney, Sartor, Arias, & Rosen, 2018;Dworkin et al, 2017;Hien et al, 2010). In contrast, self-reported substance use in the present study was moderately associated with more severe PTSD symptoms, which has also been documented in recent studies of exposure-based therapy (Hien et al 2018;Jarnecke et al, 2019). Helping patients reduce or eliminate substance use might have more benefit on their PTSD symptoms than has previously been understood.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, self‐reported substance use in the present study was moderately associated with more severe PTSD symptoms, which has also been documented in recent studies of exposure‐based therapy (Hien et al. 2018; Jarnecke et al., 2019). Helping patients reduce or eliminate substance use might have more benefit on their PTSD symptoms than has previously been understood.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results complement recent treatment research supporting the safety and utility of exposure-based treatments for adults with cooccurring SUP and PTSD. [11][12][13][14][15]20 Together findings from this and prior research demonstrate that it is safe to provide exposurebased treatment to this population when combined with substance use treatment, and this approach also may lead to the best long-term SUP and PTSD symptom outcomes.…”
Section: Discussionmentioning
confidence: 81%
“…However, no existing interventions address co-occurring SUP and PTSD symptoms among adolescents in an integrated fashion, perhaps owing to the highly compartmentalized nature of the mental health and addiction fields, the well-recognized challenges in the treatment of co-occurring SUP and PTSD symptoms across the life span, 15 and the long-standing but unsupported clinical lore asserting that engaging youth with SUP and PTSD symptoms in exposure-based treatment (criterion standard treatment for PTSD symptoms) is unsafe owing to concerns that exposure-induced distress might exacerbate SUPs. 20 Risk reduction through family therapy (RRFT) 21 was developed to address the need for an efficacious intervention for cooccurring SUP and PTSD symptoms among adolescents. An open trial 22 and a pilot randomized clinical trial (RCT) 23 supported the feasibility and preliminary efficacy of RRFT.…”
mentioning
confidence: 99%